“Antibiotics are for everyone, our past and our future generations, right? If antibiotics are dead, we will be in big trouble”: Building on community values for public engagement on appropriate use of antibiotics in Singapore - Guo, Huiling; Hildon, Zoe Jane-Lara; Chow, Angela (Frontiers in Public Health, 2022)
Introduction Shared decision-making (SDM) and trust building through continuity of care are known to play a pivotal role in improving appropriate antibiotic prescribing and use. Problem However, less is known about how to effectively leverage these factors when present - or overcome them when not - to address community needs and improve patient liaison. Methods We addressed this question using a convergent parallel mixed-methods design. Focus group discussions (N=13; August 2018─September 2020), were analysed alongside a nationally-representative cross-sectional survey (N=2004; November 2020─January 2021), in Singapore. Descriptive quantitative analyses and multivariable logistic regression were undertaken to examine antibiotic knowledge and factors associated with preference for SDM. Qualitative applied thematic analysis was integrated with these data to further explain the findings. Findings Poor knowledge and misbeliefs on appropriate antibiotic use and antimicrobial resistance (AMR) were identified. For example, only 9% of the surveyed population understood that AMR occurs when the bacteria, not the human body, become resistant to antibiotics. Qualitative data corroborated the survey findings and suggested a shared value was placed on public education to avoid the fallout from resistant bacterial strains on current and future generations. This study also identified the opportunity to harness community trust in primary care doctors, who were described as highly valued educators for antibiotic use and AMR. Those who had trust in doctors were 75% more likely to prefer SDM (aOR 1.75, 95% CI 1.10-2.77, P=0.017), especially adults aged ≥50 years who are receiving continued care with a regular doctor (aOR 1.83, 95% CI 1.18-2.86, P=0.007). Continuity of care was observed to value-add SDM by building trusting relationships, though it is often absent in younger populations. Conclusion This study highlights the long-term value-add of building on cultural capital pertaining to appropriate antibiotic use and AMR, by leveraging on the role of trust in doctors, desire for SDM and anchoring these in continuity of care when possible. Recommendations Using focused messaging and exploring alternative channels of communications such as annual check-ins or tele-consultations with a regular doctor, and emphasising continuity of care across all age groups would help bridge the identified gaps.